CHARACTERIZATION OF THE PROFESSIONAL PHYSICAL EDUCATION FIELD IN BRAZILIAN MULTIPROFESSIONAL HEALTH RESIDENCY PROGRAMS - Francisco Timbó de Paiva Neto; Anne Ribeiro Streb; Joel de Almeida Siqueira Junior; Giovani Firpo Del Duca; Cassiano Ricardo Rech (Journal of Physical Education)
ABSTRACT Multiprofessional residencies in the professional health field (MHR) are intersectoral cooperation programs to qualify health professionals. This study aimed to characterize the offer of vacancies meant for the professional Physical Education field in Brazilian MHR programs. It is a descriptive study of a documentary nature on the offer of training vacancies in MHR for the professional Physical Education field in 2022. The characterization of the programs considered: federative unit, proposing institution, total number of general vacancies, vacancies offered for Physical Education, focus of intervention of the programs, and other professional fields presented in the identified programs. A total of 184 vacancies offered by 77 MHR programs that include Physical Education in Brazil were identified. The Northeast region had the highest number of programs (n=29) and vacancies offered (n=89). Family Health was the major focus as to vacancies, while nursing appeared as the most frequent professional field among the identified programs (97.4%). This research work presented the characterization of the offer of vacancies intended for Physical Education in Brazilian MHR programs. Additionally, it evidences the need for a more equitable distribution of vacancies for Physical Education in the country.